O DIREITO PENAL SIMBÓLICO: UMA LEITURA A PARTIR DA NECESSIDADE DE SE IMPOR LIMITES AOS EFEITOS DO PODER PUNITIVO (Reflection and Critique Law Magazine, 2020)
In every historical moment, the punitive power assumes a different feature. For the illuminists, state repression should be limited through rationality. The story, however, passed-and passes-through periods in which it was assumed-and assumes-a total tendency to criminalization of conducts and recruitment of sanctions. There's no need for imagination. Moreover, the studies done by Ferri and Lombroso were never so present, and these researchers were used, albeit implicitly, as justification for a stigmatizing criminal policy. Thus, this article seeks to investigate the historical landmarks of this tendency to strengthen the punitive power, especially in relation to its segregator character. On the other hand, there is a critique of this strengthening based on questions about the real and effective effects of penal sanctions, as well as a state repressive policy.